Measuring Benefits of Hajj Zam-Zam Savings Bank Panin Dubai Syariah Bandung Through Product Quality and Service - Halim, Sugiarto; Putra, Yuda Dharma (Universitas Bina Sarana Informatika, 2025)
Reviewing the potential of the graph shows that the number of Indonesian pilgrims registering and departing for Umrah and Hajj each year continues to increase, which provides a great opportunity for Islamic travel and financial service providers. Meanwhile, one of the services that offers Hajj and Umrah Savings Products is Islamic Banking, which seeks to educate users, promote services, and improve their quality. Based on the identification of problems, it can be stated that information on Hajj savings in Islamic banking is still not evenly distributed to the wider community, and the limitations and availability of Islamic banks are still not evenly distributed in various cities. The discussion examines the development of theories that they have developed based on their knowledge and insight into the quality of Zam-Zam Hajj Savings Products at PT Bank Panin Dubai Syariah Tbk KC Bandung. This research is expected to be useful for parties who intend to save their money in Islamic banks and provide information to Islamic bank managers about how to channel customer funds properly and correctly in accordance with community regulations. and can be used as a guideline as well as additional information for the benefit of future research development.